Kecerdasan Finansial Anak Usia Dini melalui Pola Pembiasaan Transaksi Terbatas - Hanur, Binti Su'aidah; Najichah, Binti (Journal of Islamic Education, 2023)
This research tries to observe how RA Al Hidayah implemented the financial intelligence towards their early childhood students through limited transaction management habits. This research used descriptive qualititave method. Etnography study was used to analyze the data obtained. The research subject was all of early childhood students and the teachers in RA Al Hidayah Kediri. The data was collected through interview, observation and selfreport. The result of the study has shown that it was not succesfully implemented because it still requires a variety of instruments, ranging from varied methods, educational tools specifically for financial intelligence, and the creativity of educators in processing activities and materials and the biggest obstacle is minimal parental involvement, thus requiring two-way communication with parents and existing stake holders to succeed this.